2014
DOI: 10.1007/s00894-014-2421-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis of sodium-potassium alloy clusters from 7 to 55 atoms through a genetic algorithm approach

Abstract: The potential energy hypersurface associated with sodium-potassium alloy clusters is explored via an enhanced genetic algorithm, where two different operators are added to the standard evolutionary procedure. Based on the recent result that the empirical Gupta many-body potential yields reasonable results for clusters with more than seven atoms, we have employed this function in the evaluation of the energies. Agglomerates from seven to the well-established 55-atom structure are studied, and their second-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A prominent class of nanomaterials is the nanoalloy which may exhibit distinct properties from the pure metal clusters and it has application in the electronics and engineering fields [2,21]. Alloy systems are important for the development of new materials with very specific properties [22][23][24][25][26]. Sodium-lithium (Na-Li) alloy has high immiscibility in liquid phase above 573 K [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prominent class of nanomaterials is the nanoalloy which may exhibit distinct properties from the pure metal clusters and it has application in the electronics and engineering fields [2,21]. Alloy systems are important for the development of new materials with very specific properties [22][23][24][25][26]. Sodium-lithium (Na-Li) alloy has high immiscibility in liquid phase above 573 K [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the magnetic moments of the lowest energy structures with N > 17 Ti atoms (for example, 18, 25, 26, and 27 atoms) have an overall spin moment of 1 h/2π. Sodium-potassium (NaK) alloy clusters were investigated using the genetic algorithm approach by our group [26,45]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past we proposed two new operators, namely annihilator and history operators (Guimarães et al, 2002), that demonstrated along the years (Lordeiro et al, 2003; Rodrigues et al, 2008; Silva et al, 2014a,b) to be quite efficient for determining global minima in atomic and molecular cluster studies where many local minima were present. Regarding the creation of new individuals, one can observe a broad variation among methodologies available in the literature.…”
Section: Related Workmentioning
confidence: 99%
“…In the BOLS convention [15,[51][52][53][54], we choose the first and third atoms of K 44 cluster for the standard reference CN(z) for the atoms at sites of first and second atomic layers and combing the BOLS convention, we can estimated z 1 = 2.67 and z 2 = 5.12. From the relation of C(z i ) in Eq.…”
Section: N-dependence Of Nanoclustersmentioning
confidence: 99%